PENERAPAN METODE PEMBELAJARAN BUZZ GROUP UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI MIA SMA NEGERI 5 PEKANBARU - Ana Nursyarifah Nursyarifah; Elva Yasmi Amran Yasmi Amran; Armiyus Thaib Thaib (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Research on the application of learning metode of Buzz Grou has been done to achieve student’s mastery learning on the subject of chemical equilibrium in class XI Science SMAN 5 Pekanbaru. Form of research is pra-experiment research with one-shotstudy case design. Data retrieval time from the date of 14 November to 28 Novenber 2014. The sample was selected from the six existing classes, namely class XI MIA 2. Data analysis technique used is to calculate presentation of classical mastery learning. Based on the final results of data processing using acquired mastery learning classical is 87,10%, it’s means that the application of learning metode of Buzz Group can achieve student’s mastery learning on the subject of chemical equilibrium in class XI MIA.2 SMAN 5 Pekanbaru. Keywords: Buzz Group, Mastery Learning, Chemical Equilibrium.